2020
DOI: 10.1016/j.gastre.2020.07.001
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and inflammatory bowel disease: Questions arising from patient care and follow-up during the initial phase of the pandemic (February–April 2020)

Abstract: COVID-19 is a disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which was described in China in late 2019. There are currently more than three million diagnosed cases, constituting a pandemic which has caused a worldwide crisis. The devastating effects of this infection are due to its highly contagious nature and although mild forms predominate, in absolute values, the rates for severe forms and mortality are very high. The information on the characteristics of the infection in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…Spain is one of the most affected countries and this has dramatically altered care pathways in healthcare centers and, with it, our routine management of outpatients with IBD. 4 , 5 , 14 , 15 , 16 The results of our study showed that many IBD units have adapted to the circumstances using telephone and e-mail to contact their patients, and these tools have expanded their presence in clinical practice during the pandemic. They are usually considered useful and cost-effective, but the perspective of healthcare professionals with their use has not been addressed thus far.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Spain is one of the most affected countries and this has dramatically altered care pathways in healthcare centers and, with it, our routine management of outpatients with IBD. 4 , 5 , 14 , 15 , 16 The results of our study showed that many IBD units have adapted to the circumstances using telephone and e-mail to contact their patients, and these tools have expanded their presence in clinical practice during the pandemic. They are usually considered useful and cost-effective, but the perspective of healthcare professionals with their use has not been addressed thus far.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the decrease in endoscopic explorations and scheduled surgeries, the interruption of some clinical trials, as well as usual daily practice, have generated considerable concern among both patients and health professionals. 4 , 5 In Spain, because of the pandemic restrictions, many health centers activated telephone and email helplines to answer patients’ queries on the risk of infection by SARS-CoV-2, their prescribed treatment, or IBD itself.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that many patients did not receive proper healthcare throughout the pandemic, mainly because of healthcare system paralysis, but also due to fear of contact with potentially infected patients in both public and private hospitals. In fact, the fear of coronavirus disease kind of symptoms, representing multiple diseases [7][8][9][10][11]. It must be underlined that preexisting cardiovascular disease are especially prone to coronavirus infection and may undergo adverse outcomes due to the infection [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…En nuestro paciente nunca hubo síntomas respiratorios ni compromiso pulmonar, pero en esta infección viral se puede encontrar que hasta en el 61 % de los casos se presentan síntomas gastrointestinales como anorexia (35 %), diarrea (34 %) y náuseas (26 %) (8) . Esta observación recomienda que en los pacientes con EII que desarrollen síntomas digestivos nuevos durante la pandemia por SARS-CoV-2, y especialmente si es diarrea, debe considerarse esta infección dentro del diagnóstico diferencial (9) .…”
Section: Discussionunclassified